Adventitious Presence: Inadvertent Commingling and Coexistence among Farming Methods - Kershen, Drew L.; McHughen, Alan (Council for Agricultural Science and Technology (CAST), 2005)
Adventitious presence refers to the unintended commingling of trace amounts of one type of seed, or product, with another. Although this process can occur with conventionally bred crops, adventitious presence is more commonly regarded as the presence of genetically engineered (GE) seed and product in non-GE material. This document will provide a framework to discuss development of a science-based policy for adventitious presence.